Scaling for success : people priorities for high-growth organizations - Bartlow, Andrew; Harris, T. Brad (Columbia University Press, 2021)
"In today's market, businesses -- especially startups -- seek not merely growth, but hypergrowth. To deliver on this, startups must scale up accordingly, necessitating more customers, more products, and most crucially, more employees to oversee it all. Many books have been written on the scaling process, but they lack a guide for a human resources strategy to design and manage the necessary employee growth. This book will be that guide. There are four major challenges the authors aim to provide solutions for: 1 - Indecisive leadership, which leads to misplacement and ineffective deployment of employees and their requisite skills; 2 - The urge to hire people rapidly in anticipation of growth that may not come; 3 - Ambiguity in outlining roles and goals, which dissatisfies employees; 4 - "The anarchist's mirage", an impulse to avoid hierarchy derived from the start-up phase -- but organizations need structure to endure high growth periods. The authors aim to solve these problems in a work for new managers seeking a guide to building an effective talent pool and seasoned HR professionals looking to reorient themselves for new challenges alike, using the fundamentals of management and HR research combined with contemporary examples from the businesses of today"--